Effects of Ciprofloxacin and Trimethoprim on Phagocytic Activity of Polymorph Nuclear Cells, TNF-α and Complement Components Concentration in Patients with Bacterial Urinary Tract Infection - Wafaa Sadeq Al-Wazni (Journal of Global Pharma Technology, 2019)
Objective: This study was  designed to determine the effect of repeated use of Ciprofloxacin and Trimethoprim antibiotic on some signs of innate immunity of urinary tract infections’ patients such as phagocytes activity of polymorphonuclear cells in vitro and in vivo, TNF-α and Complement components concentration. Material and methods: Urine specimens were collected from 100 person (40 patients with UTI before begin treatment with antibiotics,40 patients after 3 days of treatment and 20 healthy person as control). One part of urine speciemine used for direct microscopically examination (DME) to detect the UT infection after the clinical diagnosis by specialist physician. Then second parts of the urine specimens, which gave appositive result to DME test, were cultured on blood and MacChonkey agar to isolated pathogenic bacteria and confirm sever infection in-patient. Five milliliters of blood were collected from patients (who confirmed having UTI by clinical, DME and lab culture diagnosis) to use for determine some signs of innate immunity. Results: Escherichia coli bacteria was the most common isolates (40%) from both studied groups followed by S.aureus (20%) , Pseudomonas aeruginosa and Klebsiella pneumonia (8.8%) of each and  Proteus mirabilis (2.5%). Most E.coli isolates were resistant to Trimethoprim (78%) and Ciprofloxacin (50%) antibiotics. The total WBCs count increased in patients with UTI before (13.2×106 cell/ml) and after treatment (10.5×106 cell/ml) with antibiotic compared to control (6.4×106 cell/ml) but the total WBCs count begin to decrease in patients after treatment with antibiotic in compared to patients before treatment. The result also show no significant increase in the concentration of C3(142.9,150.5 mg/dl) and C4 (26.5, 30.7 mg/dl) in patient before and after treatment respectively in compared to control but there is no noticeable deference in the concentration of these proteins between two studied groups. While the concentration of TNF-α was significantly increased in serum of patients before (256.6 pg/ml) and after (197.2 pg/ml) treatment in compared to control (155.3 pg/ml) group. Phagocytes activity of PMNs cell was evaluated by measuring the phagocytic index, a significant decrease observed in phagocytic index to reach 60% in patients before treatment and 52% in-patient after treatment compared to control group 65% after 90 minutes. Conclusions: study the effects of Trimethoprim and Ciprofloxacin on the activity of PMNs in vitro showed positive effect of Ciprofloxacin antibiotic while Trimethoprim antibiotic has negative effect on the phagocytic cells.Keywords: UTI, E. coli, PMN, Trimethoprim, Ciprofloxacin.